Parents' Perceptions of Reading, Writing, and Arithmetic Learning in Early Childhood Cognitive Development (Research in Kober Karima, Pamarican District, Ciamis Regency) - Iting Hartati; Nurjanah Nurjanah; Saepul Milah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Learning to read, write, and count (calistung) in early childhood is still a matter of debate because on the one hand it is considered important for readiness to enter Elementary School (SD), while on the other hand it is feared that it can reduce children's opportunities to play as the main learning tool. This study aims to determine parents' perceptions of learning to read, write, and count in the cognitive development of early childhood in Kober Karima. The research method used is descriptive qualitative with 15 parents selected purposively. Data were obtained through interviews, observation, and documentation, then analyzed through data reduction, data presentation, and conclusion drawing steps, and tested for validity through technical triangulation. The results of the study showed that the majority of parents (66.7%) perceived that reading, writing, and arithmetic were very important and a measure of a child's readiness to enter elementary school, while others (20%) considered it important but needed to be balanced with other developmental aspects, and only a few (13.3%) rejected early academic orientation. These findings indicate the dominance of parents' academic perceptions that impact learning practices in schools, where teachers strive to balance parental demands with the principles of play-based early childhood education. In conclusion, parental perceptions greatly influence the direction of early childhood learning, and intensive communication between teachers and parents is needed to strengthen understanding of the importance of holistic child development. It is recommended that early childhood education institutions provide socialization and learning innovations that can integrate reading, writing, and arithmetic through play activities so that children's developmental needs and parents' expectations can be aligned.